2021
DOI: 10.1007/s10856-021-06522-w
|View full text |Cite
|
Sign up to set email alerts
|

Cytocompatibility of Ti–xZr alloys as dental implant materials

Abstract: Ti–xZr (x = 5, 15, 25, 35, 45% wt%) alloys with low elastic modulus and high mechanical strength were fabricated as a novel implant material. The biocompatibility of the Ti–xZr alloys was evaluated by osteoblast-like cell line (MG63) in terms of cytotoxicity, proliferation, adhesion, and osteogenic induction using CCK-8 and live/dead cell assays, electron microscopy, and real-time PCR. The Ti–xZr alloys were non-toxic and showed superior biomechanics compared to commercially pure titanium (cpTi). Ti–45Zr had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In this study, a novel dental implant material, the Ti-45Zr alloy which has good biomechanical properties and excellent cytocompatibility [2], was studied in animal implantation experiments. Toxic and side effects, immune responses, and bone integration were systematically studied to provide the theoretical basis for Ti-45Zr alloy clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a novel dental implant material, the Ti-45Zr alloy which has good biomechanical properties and excellent cytocompatibility [2], was studied in animal implantation experiments. Toxic and side effects, immune responses, and bone integration were systematically studied to provide the theoretical basis for Ti-45Zr alloy clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…121,122 In a recent study, titanium alloyed with zirconium (Zr) has shown excellent biocompatibility and osteoconductive activity compared to pure titanium. 123 TI-6Al-4V in an untreated and bulk state has been shown to be biocompatible with fibroblasts. However, TI-6Al-4V may release vanadium and aluminum ions, which may be cytotoxic compared to pure titanium.…”
Section: Wettabilitymentioning
confidence: 99%
“…This was further corroborated by reactive oxygen species (ROS) tests and inflammatory responses where the alloy significantly increased ROS generation in HGF and facilitated the up-regulation of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-8). Titanium, however, has been generally shown to be cytocompatible due to its inertness and superior corrosion resistance. , In a recent study, titanium alloyed with zirconium (Zr) has shown excellent biocompatibility and osteoconductive activity compared to pure titanium . TI-6Al-4V in an untreated and bulk state has been shown to be biocompatible with fibroblasts.…”
Section: Implant Characteristicsmentioning
confidence: 99%
“…The hardness of the Ti-Zr alloys increased with increasing Zr content and ranged from 266 HV (Ti-10Zr) to 350 HV (Ti-40Zr) (Ho et al, 2008). Ti-45Zr has the optimum strength/elastic modulus ratio and osteogenic activity, which would be advantageous for reducing the fracture risk of implant materials (Ou et al, 2021). Due to these properties, Ti-Zr alloys are suitable for making narrow dental implants (NDIs), which are an alternative treatment when there is insufficient bone for regular implants (Gonzalez-Valls et al, 2021).…”
Section: Ti-zr-cu Alloysmentioning
confidence: 99%